2020
DOI: 10.1590/0037-8682-0274-2019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of four malaria rapid diagnostic tests, Vikia Malaria Pf/Pan, Meriline-Meriscreen Pf/Pv/Pan, Right Sign Malaria Pf/Pan, and Right Sign Malaria Pf, among febrile patients in Gabon

Abstract: Introduction: Rapid diagnostic tests (RDTs) are selected based on their performances. Here, we compared the diagnostic performance of different malaria RDTs. Methods: Febrile patients were tested for malaria using Vikia Malaria Pf/Pan, Meriline-Meriscreen Pf/Pv/Pan, Right Sign Malaria Pf/Pan, and Right Sign Malaria Pf RDTs at Melen Regional Hospital in Gabon. Results: In total, 120 of 274 tested children (43.8%) had malaria. The sensitivity was > 95% for all RDTs, while the specificity was > 85% for two tests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In our work we used an RDT which has been evaluated by the WHO [25,26], and our results have shown high sensitivity (94.74%) in the detection of infections by P. falciparum, except in one patient with low parasitemia. These are similar results to those were reported by other RDTs applied to fresh blood samples that show a sensitivity of around 95% of the cases confirmed by microscopy [27][28][29][30] Pan-specific pLDH detection showed a lower sensitivity, 12 of 19 patients (63.16%), which is slightly higher than that reported in low transmission seasons (58.0%) in Niger [31]. These results could point to the possibility of a mixed infection, but it is highly unlikely according to the epidemiological data offered by the WHO [32], which indicate that the 100% of cases reported in Rwanda in the last year were confirmed as simple P. falciparum infections.…”
Section: Discussionsupporting
confidence: 91%
“…In our work we used an RDT which has been evaluated by the WHO [25,26], and our results have shown high sensitivity (94.74%) in the detection of infections by P. falciparum, except in one patient with low parasitemia. These are similar results to those were reported by other RDTs applied to fresh blood samples that show a sensitivity of around 95% of the cases confirmed by microscopy [27][28][29][30] Pan-specific pLDH detection showed a lower sensitivity, 12 of 19 patients (63.16%), which is slightly higher than that reported in low transmission seasons (58.0%) in Niger [31]. These results could point to the possibility of a mixed infection, but it is highly unlikely according to the epidemiological data offered by the WHO [32], which indicate that the 100% of cases reported in Rwanda in the last year were confirmed as simple P. falciparum infections.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, if only a single-colored line on the control line ‘C’ is interpreted as negative results. Results were deemed invalid if any color could not be found on the control line [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the number of false-positive results were ranging between 14.1 -17.5% depending on the specific RDTs. Further the number of false-negative results were less than 5% of febrile cases of total population [ 19 ]. For the RDT that we used the sensitivity and specificity was reaching > 99.9% which shows the most likely cause of false negative results was due to sample error including how the sample was stored and delivered.…”
Section: Discussionmentioning
confidence: 99%
“…Ditombi et al [50] compared four RDTs for malaria and found that all RDTs had a sensitivity >95%, with only two tests showing specificity above 85%. With the inclusion of the WHO Methods Manual for product testing of malaria rapid diagnostic tests [51], the quality and trust in RDTs improved.…”
Section: Malaria Rapid Diagnostic Testingmentioning
confidence: 99%